Implementasi Mikrokontroler ESP32 Dan Sensor Kualitas Air Dalam Sistem Monitoring Lingkungan Berbasis Internet of Things - Azis, Abdul; Sujono, Sujono (Jurnal Manajemen Sistem Informasi (JMASIF), 2026)
This study develops an Internet of Things (IoT)-based water quality monitoring system using the ESP32 microcontroller integrated with pH and turbidity sensors to overcome the limitations of manual observation. The system is designed to measure water parameters periodically and transmit the data via a Wi-Fi connection to a web-based dashboard. Through this interface, users can observe water conditions remotely without direct presence at the measurement site. The development process includes hardware integration, sensor data processing, and network communication testing. The evaluation results indicate that the sensors achieve an accuracy rate of 92.4% when compared with standard measurement instruments, while the data transmission success rate reaches 98% under various network conditions. The system is also capable of providing early warnings when parameter changes indicate potential water contamination. These results demonstrate that the proposed system can function as an efficient and practical tool for monitoring water quality. In addition, it supports faster decision-making in maintaining environmental water conditions.